Exploring the issues, practices, and prospects of family planning among married couples in Southern Philippines - Sittie Mairah H. O Ali; Ashley A. Bangcola; Athena Jalaliyah Derico Lawi (Belitung Nursing Journal, 2022)
Background: Nurses are involved in all aspects of health, including reproductive health. They play a fundamental role in family planning and are often designated as point persons in family planning-related concerns. In order to provide effective counseling on family planning, the nurse must understand issues, practices, and prospects of family planning among married couples in their community. Objective: This exploratory multiple case study investigates family planning issues, practices, and prospects among couples in a municipality located in Southern Philippines. Methods: Ten married couples of varying characteristics were interviewed to elicit their perspectives on family planning practices. The data were analyzed using coding transcriptions and thematic analysis. Results: Five sub-themes emerged under the theme of Family Planning Issues: family planning as a burden; fear of side effects; peer-driven contraceptive choice; family planning as a social stigma; family planning as a sin. Two sub-themes emerged under the theme of Family Planning Practices: knowledge of family planning commodities; availability and acceptance of the contraceptive method. Finally, two sub-themes also emerged under the theme of Family Planning Prospects: family planning as a financially beneficial practice; prospects on family planning depend on husband’s acceptance. Conclusion: These sub-themes were also distinguished by their similarities and differences based on the four parameters identified, including age, sex, financial status, and educational attainment, which aided in the development of recommendations that could be implemented in the local community. The results of this study especially have a bearing on nurses and their role in the family planning process. Nurses play a fundamental role in guiding community members and families toward health and wellness. Thus, it is crucial for nurses to understand family planning issues underpinning their community so they can better exercise their role.